Giant sigmoid diverticulum with coexisting metastatic rectal carcinoma: a case report - Sasi, Walid (BioMed Central, 2010)
INTRODUCTION: Giant diverticulum of the colon is a rare but clinically significant condition, usually regarded as a complication of an already existing colonic diverticular disease. This is the first report of a giant diverticulum of the colon with a co-existing rectal carcinoma. CASE PRESENTATION: We report a case of a 66-year-old Caucasian woman who presented with lower abdominal pain, chronic constipation and abdominal swelling. Preoperative abdominal computed tomography revealed a giant diverticulum of the colon with a coexisting rectal carcinoma and pulmonary metastasis revealed on a further thoracic computed tomography. An en bloc anterior resection of the rectum along with sigmoid colectomy, partial hysterectomy and right salpingoophorectomy was subsequently performed due to extensive adhesions. CONCLUSION: This report shows that the presence of a co-existing distal colorectal cancer can potentially lead to progressive development of a colonic diverticulum to become a giant diverticulum by increasing colonic intra-luminal pressure and through the ball-valve mechanism. This may be of interest to practising surgeons and surgical trainees.